2020
DOI: 10.3390/educsci10040105
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Courses and Teacher Training Programs on Playful Methodology in Andalusia (Spain)

Abstract: In this study we analyzed the primary teaching and training experiences that observe play as a didactic resource to facilitate learning, highlighting fundamental elements and characteristics. A descriptive analysis of the different programs and contents with respect to playful methodology proposed by the Ministry of Education of Andalusian Government (Spain) is presented. The purpose of this type of descriptive idiographic research is to define, classify, catalogue, or characterize the experiences of innovatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
1
4
0
2
Order By: Relevance
“…Taking into account the limitation of the sample, especially for some specialties such as physics and chemistry, which makes it difficult to generalize the results, this study has shown that the activity based on projects is adequate for training future secondary school teachers in research matters regardless of the specialty, which may initially seem crucial for establishing specific training activities. Thus, this research work demonstrates that this type of multidisciplinary activity is adequate for all the students belonging to the different STEM specialties, corroborating previous studies applying multidisciplinary methodologies [25,26]. Furthermore, this type of multidisciplinary activity reinforces the necessities exposed in previous papers related to training teachers in Spain [24].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Taking into account the limitation of the sample, especially for some specialties such as physics and chemistry, which makes it difficult to generalize the results, this study has shown that the activity based on projects is adequate for training future secondary school teachers in research matters regardless of the specialty, which may initially seem crucial for establishing specific training activities. Thus, this research work demonstrates that this type of multidisciplinary activity is adequate for all the students belonging to the different STEM specialties, corroborating previous studies applying multidisciplinary methodologies [25,26]. Furthermore, this type of multidisciplinary activity reinforces the necessities exposed in previous papers related to training teachers in Spain [24].…”
Section: Discussionsupporting
confidence: 88%
“…Nonetheless, although recent articles reveal the necessity of designing new methodologies to enhance the educational research skills of students of a Master's Degree in Secondary Education (future teachers) [23,24], there are hardly any references to experiences with or research on such a specific topic. Some of the previous articles related to similar interests are linked to the application of multidisciplinary methodologies [25,26], those most appreciated by teacher candidates being related to new or improved methodologies and the use of updated technology in the classroom [27][28][29]. The Some of the previous articles related to similar interests are linked to the application of multidisciplinary methodologies [25,26], those most appreciated by teacher candidates being related to new or improved methodologies and the use of updated technology in the classroom [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the study of teacher training courses and programmes helps to understand if it can really promote improvement in classroom practices and meaningful student learning. By using games as a didactic resource, it is possible to work on the different educational levels and it can become a key tool for educators (Baneres et al, 2008;Higueras-Rodriguez, Medina-Garcia & Molina-Ruiz, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Según Assmann (2002), el verdadero cambio en la enseñanza es la unión del aprendizaje y la motivación. Esta unión hará que el proceso de enseñanza-aprendizaje sea más ameno y atractivo, además de mucho más efectivo (Higueras-Rodríguez et al, 2020).…”
Section: Introductionunclassified